Essential minerals for good heath, but their overdose is not - Yap, Chee Kong (2017)
Present review paper focussed on the essential metals Cu and Zn in the marine mussels by oral human consumption based on estimated daily intakes (EDI) and target hazard quotient (THQ) for both metals. The values of EDI and THQ have been re-calculated with the cited data of Cu and Zn from 8 publications with four marine mussel species. It is found that high level mussel consumers have higher values of EDI and THQ, when compared to average level mussel consumers. The uncontrolled intake of contaminated mussels could result in THQ value > 1, indicating negative health implications during a life span in a human population. Therefore, this finding indicated both metals, although are essential minerals for good health, their overdose is not.